Dreams and COVID-19 - Di Renzo, Magda; Tagliacozzi, Bruno (Journal of analytical psychology, 2021)
This work originates from reflections on the observation of recurring themes in dreams of patients in psychoanalytic treatment during the most restrictive lockdown period in Italy (March ‐ May 2020). The authors focus on the peculiar dialogic state between consciousness and the unconscious that arose following a collective event such as that of the pandemic, which determined the activation of complex personal nuclei, compensatory effects of the unconscious psyche and new perspective functions. These latter aspects are interpreted with reference to the contributions of Erich Neumann, bringing a new psychological vision of the relationship between Man and Nature in relation to catastrophic events. Ce travail a pour point de départ nos réflexions sur l’observation de thèmes récurrents dans les rêves de patients en traitement psychanalytique durant la période de confinement le plus strict en Italie (de mars à mai 2020). Les auteurs se concentrent sur l’état dialogique singulier entre la conscience et l’inconscient, qui survient à la suite d’un événement collectif tel la pandémie, et qui détermine l’activation de noyaux personnels complexes, les effets compensatoires de la psyché inconsciente et les fonctions de nouvelle perspective. Ces derniers aspects sont interprétés en référence aux apports d’Erich Neumann, amenant une nouvelle vision psychologique de la relation entre l’Homme et la Nature en lien avec des événements catastrophiques. Diese Arbeit basiert auf Überlegungen zur Beobachtung wiederkehrender Themen in Träumen von Patienten in psychoanalytischer Behandlung während des restriktivsten Lockdowns in Italien (März ‐ Mai 2020). Die Autoren konzentrieren sich auf den besonderen dialogischen Zustand zwischen Bewußtem und Unbewußtem, der in der Folge eines kollektiven Ereignisses wie dem der Pandemie entstand, das die Aktivierung persönlicher Komplexkerne, kompensatorische Effekte der unbewußten Psyche und neuer perspektivischer Funktionen hervorrief. Diese letzteren Aspekte werden unter Bezugnahme auf die Beiträge von Erich Neumann interpretiert und erbringen eine neue psychologische Sicht auf die Beziehung zwischen Mensch und Natur hinsichtlich katastrophaler Ereignisse. Questo lavoro nasce dalle riflessioni sull'osservazione di temi ricorrenti nei sogni dei pazienti in analisi durante il periodo di lockdown restrittivo in Italia (marzo‐maggio 2020). Gli Autori si focalizzano sul particolare stato dialogico tra conscio ed inconscio che è emerso a seguito di un evento collettivo quale la pandemia, che ha determinato l'attivazione di nuclei complessuali personali, effetti compensatori dell'inconscio e nuove funzioni prospettiche. Proprio queste ultime vengono interpretate in riferimento ai contributi di Erich Neumann, ed offrono una nuova visione psicologica della relazione tra Uomo e Natura in relazione ad eventi catastrofici. Истоками работы стали размышления о повторяющихся темах в сновидениях пациентов, проходивших психоанализ в период самого строгого в Италии локдауна (март – май 2020). Авторы обращают внимание на особое состояние диалога между сознанием и бессознательным, которое возникает в результате коллективного события, например, пандемии, и обуславливает активацию комплексных личных ядер, компенсаторных эффектов в бессознательном и новых перспективных функций. Упомянутые аспекты интерпретируются в соответствии с представлениями Эриха Нойманна, который привнес новое психологическое видении в отношения между Человеком и Природой в ситуации катастрофических событий. El presente trabajo se origina a partir de reflexiones basadas en la observación de temas recurrentes en sueños de pacientes en tratamiento psicoanalítico durante el período de cuarentena de mayor restricción en Italia (Marzo‐Mayo 2020). Los autores focalizan en el estado dialógico peculiar entre la consciencia y el inconsciente que emergió a partir de un evento colectivo como el de la pandemia, el cual determinó la activación de núcleos de complejos personales, efectos compensatorios de la psique inconsciente y nuevas funciones. Estos últimos aspectos son interpretados con referencia a las contribuciones de Erich Neumann, ofreciendo una nueva visión psicológica de la relación entre el Hombre y la Naturaleza con relación a los eventos catastróficos. 梦与新冠 这篇文章来自对反复出现的梦的主题的反思, 这些梦是意大利(2020年3月至5月)最严格的封城期间, 接受心理分析治疗的病人们做的。作者关注在类似疫情这种集体事件之后, 唤起的意识与无意识之间特定的对话性的状态, 这一对话性的状态决定了复杂的个人核心的激活, 无意识心灵的补偿作用, 及产生新视角的功能。后面提及的这个功能, 在文章中参考埃里希‐诺伊曼 (Erich Neumann)的贡献, 进行了解释, 其中带入了一个新的视角来看待在灾难事件中人与自然的关系。